Angka kejadian ambliopia pada usia sekolah di SD Negeri 6 Manado - Saputri, Fikryah E.; Tongku, Yamin; Poluan, Herny (e-CliniC, 2016)
Abstract: Amblyopia is the reduced of visual acuity in one or both eyes despite had been corrected with spectacles without any structural abnormalities of the eye and the rear sight path. Amblyopia occurs in about 2-3% of the population, but lacking of concern will lead to detrimental life. This study was aimed to obtain the prevalence of amblyopia in elementary school students of SD Negeri 6 Manado. This was a descriptive study with a cross-sectional design. Samples were 317 elementary school students aged 6-12 years old. Data were obtained by using auto refractometer and Snellen chart as well as pinhole test to assess the eyes disorders. The results showed that of all respondents there were 7 students (2%) with amblyopia. Based on the age of the incidence of amblyopia there were 3 students of 8 years old (43%) and 1 student each in the age of 7 years, 9 years, 11 years, and 12 years (14.25%). Amblyopia was found in 4 (57%) female students and 3 (43%) male students. Further studies are needed with a larger coverage area to obtain the prevalence of amblyopia more accurately. Keywords: amblyopia, prevalence, school-age children Â  Abstrak: Ambliopia adalah berkurangnya ketajaman penglihatan pada satu atau kedua mata walaupun sudah dengan koreksi kacamata terbaik tanpa kelainan struktur pada mata maupun lintasan penglihatan bagian belakang. Ambliopia merupakan masalah dalam penglihatan pada 2-3% populasi, tapi bila dibiarkan akan sangat merugikan kehidupan penderita. Penelitian ini bertujuan untuk mengetahui angka kejadian ambliopia di SD Negeri 6 Manado. Jenis penelitian ialah deskriptif dan pengumpulan data dilakukan secara potong lintang. Sampel ialah 317 siswa berusia sekolah 6-12 tahun. Pengambilan data dengan menilai kelainan refraksi menggunakan auto refrraktometer dan Snellen chart serta pinhole untuk menilai kelainan pada mata. Hasil penelitian mendapatkan dari seluruh responden didapatkan 7 anak (2%) mengalami ambliopia. Berdasarkan usia, angka kejadian ambliopia pada usia 8 tahun sebanyak 3 anak (43%) dan pada usia 7 tahun, 9 tahun, 11 tahun serta 12 tahun sebanyak 1 anak (14,25%). Berdasarkan jenis kelamin angka kejadian ambliopia pada perempuan yaitu 4 anak (57%), sedangkan laki-laki sebanyak 3 anak (43%). Studi lanjut diperlukan dengan cakupan wilayah dan jumlah sampel yang lebih luas sehingga mendapatkan nilai prevalensi ambliopia yzng lebih akurat. Kata kunci: ambliopia, angka kejadian, anak usia sekolah